Rytualne i nierytualne oblicze „fali” w szkole - Jaskulska, Sylwia (Studia Edukacyjne, 2017)
In the paper I ask whether the similarities between the institutional hazing and tribal rites of initiation, pointed to by authors who describe this phenomenon, make it possible to talk about a ritual character of the brutal phenomenon of how freshmen are treated by older students, and if they do, then how can it translate into potential preventive measures. I discuss this issue based on the example of hazing at school. Having chosen the distinctive features of the rites of passage as my point of reference, I refer to school hazing as a pseudo-rite and I recommend taking into account its ritual character and the non-ritual objectives it completes in the preventive and repair measures at school.